Ankylosing spondylitis: beyond genome-wide association studies. Issue 4 (July 2016) - O'Rielly, Darren D.; Uddin, Mohammed; Rahman, Proton
Abstract : Purpose of review: This article discusses genomic investigations in ankylosing spondylitis (AS) beyond genome-wide association (GWA) studies, but prior to this, genetic variants achieving genome-wide significance will be summarized highlighting key pathways contributing to disease pathogenesis. Recent findings: Evidence suggests that disease pathogenesis is attributed to a complex interplay of genetic, environmental and immunological factors. GWA studies have greatly enhanced our understanding of AS pathogenesis by illuminating distinct immunomodulatory pathways affecting innate and acquired immunity, most notably the interleukin-23/interleukin-17 pathway. However, despite the wealth of new information gleaned from such studies, a fraction of the heritability (24.4%) has been explained. This review will focus on investigations beyond GWA studies including copy number variants, gene expression profiling, including microRNA (miRNA), epigenetics, rare variants and gene–gene interactions. Summary: To address the 'missing heritability' and advance beyond GWA studies, a concerted effort involving rethinking of study design and implementation of newer technologies will be required. The coming of age of next-generation sequencing and advancements in epigenetic and miRNA technologies, combined with familial-focused investigations using well-characterized cohorts, is likely to reveal some of the hidden genomic mysteries associated with AS.